PENGARUH PEMBANGUNAN INFRASTRUKTUR PENDIDIKAN TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI SUMATERA UTARA - Mariatul Kubtiyah Ritonga (Institut Pendidikan Tapanuli Selatan, 2017)
Economic Growth in North Sumatera priod 2001 until 2012 shows the condition that increases continuously, but the increase did not have an impact on education, health. This study aimed to analyze the influence of the education infrastructure to economic growth in the province of North Sumatra simultaneously and partially. The data used are secondary data from BPS in North Sumatra time series from 2001 till 2012. Data analysis was correlation product moment regression models estimated with the help of the program SPSS.. The results of this study showed that simultaneous variable education infrastructure and have a significant effect on economic growth in the province North Sumatra. While partially concluded that variablesss educational infrastructure but not significant positive effect on economic growth in the province of North Sumatra. The results of this study also showed that the most dominant variables to economic growth in the province of North Sumatra is the total population.